2017
DOI: 10.1074/jbc.m117.796912
|View full text |Cite
|
Sign up to set email alerts
|

IRAK4 kinase activity controls Toll-like receptor–induced inflammation through the transcription factor IRF5 in primary human monocytes

Abstract: Interleukin-1 receptor-associated kinase 4 (IRAK4) plays a critical role in innate immune signaling by Toll-like receptors (TLRs), and loss of IRAK4 activity in mice and humans increases susceptibility to bacterial infections and causes defects in TLR and IL1 ligand sensing. However, the mechanism by which IRAK4 activity regulates the production of downstream inflammatory cytokines is unclear. Using transcriptomic and biochemical analyses of human monocytes treated with a highly potent and selective inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 43 publications
5
62
0
Order By: Relevance
“…Second, the MAPK pathways are induced downstream of the TAK1 complex leading to activation of the transcription factors activator protein‐1 (AP‐1) and CREB. Third, TRAF6 facilitates activation of IFN regulatory factor 5 (IRF5) via a TAK1‐IKK‐β axis . The activation and cooperative binding of these transcription factors to specific gene promoters culminates in production of potent proinflammatory cytokines and chemokines that elicit an acute inflammatory response.…”
Section: An Overview Of Tlr Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the MAPK pathways are induced downstream of the TAK1 complex leading to activation of the transcription factors activator protein‐1 (AP‐1) and CREB. Third, TRAF6 facilitates activation of IFN regulatory factor 5 (IRF5) via a TAK1‐IKK‐β axis . The activation and cooperative binding of these transcription factors to specific gene promoters culminates in production of potent proinflammatory cytokines and chemokines that elicit an acute inflammatory response.…”
Section: An Overview Of Tlr Signalingmentioning
confidence: 99%
“…Reconstitution of IRAK4 ‐deficient human fibroblasts with IRAK4‐KI (K213A/K214A), also restores NF‐κB and AP‐1 luciferase activity similarly to WT IRAK4 . Additionally, whereas NF‐κB and MAPK activation is reported to be only moderately affected following TLR activation in the presence of IRAK4 kinase inhibition in human monocytes, IRF5 activation and subsequent nuclear translocation is inhibited . Because the expression of most cytokine genes requires cooperative binding of both IRF5 and NF‐κB within promoter regions, the loss of activated IRF5 significantly reduces cytokine expression .…”
Section: The Main Players In Early Myd88‐dependent Tlr Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we have shown that whereas complete inhibition of IRAK4 autophosphorylation has minimal effects on IL-1-induced cytokines and MAPK and NF-B signaling, it has profound effects on TLR-induced cytokines (7). Recently, we demonstrated that cytokines produced by TLR signaling in monocytes are controlled by the IRAK4 kinase-dependent activation of the transcription factor IRF5 (11). However, the precise role of IRAK4 in IL-1 signaling is still not completely understood.…”
Section: Interleukin-1 Receptor (Il1r)-associated Kinase 4 (Irak4) Ismentioning
confidence: 99%
“…Subsequently, we found that the inhibition of ROCK/P38MAPK and NF-κB and activation can obviously . Further more, IKKβ activation can lead to the nuclear translocation of IRF5 and induction of inflammatory cytokines in human monocytes [52]. IRF5 can directly bind to DNA in the 5' upstream region of the TNF, its recruitment to the 3' downstream region of the TNF gene depends on the protein-protein interactions with NF-κB RelA [53].…”
Section: Discussionmentioning
confidence: 99%